From Ballarat to Bangkok: how can cross-sectoral partnerships around the Sustainable Development Goals accelerate urban liveability?. Issue 2 (3rd May 2020) - Horne, Ralph; Correia, Joana; Badland, Hannah; Alderton, Amanda; Higgs, Carl
ABSTRACT: The UN Global Compact – Cities Programme sponsors cross-sectoral partnerships to further the Sustainable Development Goals and the New Urban Agenda at the local level. The paper situates urban liveability and action on it at the local level through the Sustainable Development Goals. It describes a City Partnerships Australia project (Ballarat) and a Bangkok liveability project, and explores findings to date. Here we are concerned with cities that have already committed to work together to co-design, build capacity and deliver city projects to enhance urban liveability, addressing the key city challenges of inequality, accountability and sustainability. This practice paper documents and reflects upon two partnered projects and, in particular, the prospects for their contribution to liveability and related public health outcomes. Across arenas of governance, scale and thematic priorities, cities face common challenges and capability needs. This cross-case assessment provides insights into the efficacy of the Sustainable Development Goals and the New Urban Agenda as common platforms for the necessarily wide range of interest groups required to progress liveability projects in the regional city of Ballarat, Australia, and Bangkok, Thailand.